An integrated approach of analytical hierarchy process and GIS for site selection of urban parks in Iskandar Malaysia - Rasli, F. N. (Association for Geoinformation Technology, 2016)
Rapid urbanisation with increasing population, transportation and industrial activities are responsible for many environmental problems including global warming and climate change. Increasing green spaces in cities was among various formulated strategies to curb the issue, which can help to reduce the urban temperature by absorbing atmospheric carbon dioxide (CO2) and providing thermal comforts. The objective of this study is to find suitable locations for developing urban parks in Iskandar Malaysia (IM), as since its establishment in 2006, IM has been undergoing rapid urbanisation and high demand in varieties of sectors which lead to high emission of greenhouse gases (GHG) and high temperature in the area. In this study, the guidelines set by the Department of Town and Regional Planning (JPBD) Peninsular Malaysia are used to integrate parameters such as park size, distance from main roads and topography for selecting suitable areas for parks development in IM. An integrated approach combining Analytical Hierarchy Process (AHP) and Geographic Information Systems (GIS) is adopted to provide weightages for each of the parameter layer by providing scoring and ranking to each parameter and conducting weighted overlay analysis to identify suitable locations for six different types of parks. In the final site suitability map, it reveals that although 623 areas show high suitability for park development, only 27 of them lie near the water bodies where all the water bodies in this study consist of rivers. Based on the obtained results, these locations can be proposed to the Municipal Councils in IM for development of new parks. The parks within the cities can act as a very good medium of cooling with the presence of trees to store and sequester excess CO2 and the presence of water bodies to reduce the ambient air temperature. However, the final decision to consider these suitable locations for future developments of parks still depends on the local authorities.